Thiophene-S doping assisted constructing high-performance pitch-based hard carbon anode for sodium-ion batteries - Dong Sun; Lu Zhao; Yin Yang; Changbo Lu; Chunming Xu; Zhihua Xiao; Xinlong Ma (Materials Reports: Energy)
Hard carbon has emerged as a promising anode material for sodium-ion batteries (SIBs) due to its exceptional chemical stability and abundant resources. However, its application in energy storage is limited by the poor fast-charging performance caused by the slow Na+ reaction kinetics. Herein, thiophene-S doped oxidized pitch (SOP-600) with outstanding fast-charging performance has been fabricated via a facile ball milling and carbonization procedure. Benefiting from the high thiophene-S doping content, the optimized SOP samples (SOP-600) exhibit plentiful active sites and a rich micro-mesoporous structure with rapid ion transport channels, significantly enhancing the Na+ reaction kinetics and improving the fast-charging performance. When employed as SIBs anode, SOP-600 delivers an impressive specific capacity of 690.3 mAh g−1 at 0.05 A g−1. In addition, it maintains a significant reversible capacity of 373.5 mAh g−1 at 7 A g−1 with a capacity retention rate of 54.1%, demonstrating excellent fast-charging performance. Moreover, SOP-600 anode exhibits a remarkable cycling capacity of 490.7 mAh g−1 under 1 A g−1, with 92.5% capacity retention after 1000 cycles, highlighting its robust structural stability. Furthermore, sodium ion hybrid capacitors (SICs) assembled with SOP-600 anode and activated carbon cathode achieve a high reversible capacity of 53.5 mAh g−1 at 1 A g−1. This work provides theoretical insights into how thiophene-S doping enhances the fast-charging performance of hard carbon in SIBs.